(untitled) (Research Journal, 2025)
In the banking industry, work-related stress is a major problem that has an impact on employee well-being and performance. This study looks at the stress levels of employees at three government banks in the Ilam district: Agriculture Development Bank, Rastriya Banijya Bank Limited, and Nepal Bank Limited. The Perceived Stress Scale (PSS) and work-related questionnaires were used to analyze a sample of 25 employees. The results show that the majority of workers have moderate levels of stress, and that there is a bidirectional causal relationship and a significant positive correlation between personal stress and stress at work. Excessive workload, poor coordination, poor communication, unclear job responsibilities, and time management issues are major stressors. Nonetheless, job satisfaction, collaboration, and workplace support all help to lower stress levels. The study emphasizes how crucial it is to placed structured stress management techniques into practice, such as better communication, defined roles, and strengthened organizational support networks. By addressing these issues, the banking industry can increase overall productivity, decrease stress-related inefficiencies, and improve employee well-being.